2014
DOI: 10.1111/iju.12609
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerance of one‐third full dose bacillus Calmette–Guérin maintenance therapy every 3 months or 6 months: Two‐year results of URO‐BCG‐4 multicenter study

Abstract: Abbreviations & Acronyms Objectives:To assess bacillus Calmette-Guérin maintenance treatment schedule for nonmuscle invasive bladder cancer at 2 years, using one-third of the full dose and fewer instillations every 3 months or 6 months. Methods: This was a prospective, randomized, multicenter study. All patients had an intermediate-or high-risk non-muscle invasive bladder cancer. They received three weekly instillations of one-third dose bacillus Calmette-Guérin every 6 months (group I) and two weekly instilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…In support to our data, the use of one-half or one-third of BCG for standard instillation has recently been proposed. A study in NMIBC-patients treated with low dose BCG had lower toxicity and higher quality of life compared with NMIBC-patients instilled with standard-dose [57, 58]. Thus, low dose BCG can be applied to different BCG research fields of interest including mycobacterial infections, cancer immunotherapy, and prevention of autoimmunity and allergies [59].…”
Section: Discussionmentioning
confidence: 99%
“…In support to our data, the use of one-half or one-third of BCG for standard instillation has recently been proposed. A study in NMIBC-patients treated with low dose BCG had lower toxicity and higher quality of life compared with NMIBC-patients instilled with standard-dose [57, 58]. Thus, low dose BCG can be applied to different BCG research fields of interest including mycobacterial infections, cancer immunotherapy, and prevention of autoimmunity and allergies [59].…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose BCG maintenance regimens with a reduced number of instillations have been investigated in 2 RCT studies; it was found in the reduced instillation group that treatment was effective with no impact on tumor recurrence or progression. 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, leukocytes, recruited and mi- grated into the bladder during the immunological response to BCG [16] , were postulated to predict the recurrence-free survival [17,18] . However, the URO-BCG-4 study did not confirm these findings [19] .…”
Section: Evidence Synthesis Does Abu Increase the Risk Of Febrile Utimentioning
confidence: 88%